Empowerment-Based Palliative Care to Improve Psychological Well Being and Quality of Life in Women with Breast Cancer - Fathiya Lutfil Yumni; Siswanto Agung Wijaya; Diah Priyantini; Chlara Yunita Prabawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Patients with breast cancer at the terminal stage often experience a decrease in quality of life and problems in psychological well-being. Management of patients with terminal illnesses requires end-of-life care, which is comprehensive care for chronic diseases that are nearing death, which involves multidisciplinary collaboration of health workers with the main focus of care being a peaceful death. The aim of this research is to develop empowerment-based palliative care to improve psychological wellbeing and quality of life of breast cancer patients. Explanatory research with a cross sectional approach to develop a model. The sample of this study were 125 breast cancer patients. The variables in this study consisted of self- management, delivery systems, decision support, clinical information, community resources, palliative care, empowerment, quality of life and spiritual wellbeing which were measured using a modified questionnaire whose validity and reliability were measured. The data were then analyzed using Smart PLS and used in formulating strategic issues for focus group discussions and expert consultations. The output of this study was an empowerment-based palliative care module on the quality of life and psychological well-being of breast cancer patients as well as scientific publications in the Scopus International journal, a module that already prepared will be arranged in the ISBN and Intellectual Property Rights